Development of a low pressure Pneu-Nets actuator using room temperature vulcanizing silicon rubber - Nur Rahmah Abdullah; Sylvi Febriana Rachmawati Irnadiastputri; Mohammad Ikhsan (IAES International Journal of Robotics and Automation (IJRA), 2026)
Soft robotics offers potential advantages in achieving safer human-robot interaction compared to conventional rigid robots, making it relevant for stroke rehabilitation applications. A major challenge in developing soft actuators lies in selecting materials that balance mechanical performance and practical fabrication. This study investigates room-temperature vulcanizing (RTV) silicone rubber as an alternative to platinum-cured silicone rubber for Pneumatic-Networks (Pneu-Nets) actuators fabrication. The actuator was developed through mold casting with 3D-printed molds and characterized by its contact force and bending angle. This actuator produced a maximum force of 0.93 N and a bending angle of 244.5° at 52 kPa. Finite element analysis (FEA) was performed to simulate its mechanical behavior and validate experimental results. The simulation errors were quantified as 8.3% for contact force and 19.3% for bending angle at 30 kPa, confirming the feasibility of using condensation-cured silicone rubber for efficient soft actuator production.